EFFECT OF 2% CHLORHEXIDINE GLUCONATE ON THE DEGRADATION OF RESINCOMPOSITEâ€“DENTIN BOND STRENGTH WHEN USING SELF-ETCH ADHESIVE SYSTEMS - Puspitasari, Dewi; Herda, Ellyza; Soufyan, Andi (International Journal of Applied Pharmaceutics, 2018)
Objective: The purpose of this study was to analyze the effect of 2% chlorhexidine gluconate (CHX) on the degradation of composite resinâ€“dentin bond strength when using self-etch adhesive systems. Methods: CHX (2%) was applied before application of two-step self-etch (TSC) and one-step self-etch (OSC) adhesive. Resin composite was applied incrementally. Specimens from the degradation treatment group were immersed in 10% NaOCl for 1 h. Shear bond strength was tested with a universal testing machine and analyzed using one-way ANOVA and Dunnett's T3 post-hoc test. The composite resinâ€“dentin bonds were observed using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Results:Â In the treatment group without 10% NaOCl, shear bond strength values were higher in the 2% CHX-treated group (TSC 11.67Â±1.76 MPa and OSC 10.19Â±1.44 MPa) than in the untreated group (TSC 10.93Â±1.31MPa and OSC 9.97Â±1.41 MPa), although this difference was not statistically significant. In samples exposed to10% NaOCl, shear bond strength values were higher in the 2% CHX-treated group (TSC 11.14Â±1.22 MPa and OSC 9.95Â±1.21 MPa) than in the untreated group (TSC 10.08Â±0.45 MPa and OSC 8.62Â±0.85 MPa), although this difference was not statistically significant. The SEM of samples from the 2% CHX-treated group showed less degradation than samples from the untreated group did. Conclusion:Â Application of 2% CHX may decrease the degradation of the resin composite-dentin bond.